2009
DOI: 10.1053/j.gastro.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Colitis-Associated Variant of TLR2 Causes Impaired Mucosal Repair Because of TFF3 Deficiency

Abstract: Background & aims Goblet cells (GC) facilitate mucosal protection and epithelial barrier repair, yet the innate immune mechanisms that selectively drive GC functions have not been defined. The aim of this study was to determine whether TLR2 and modulation of GC-derived TFF3 are functionally linked in the intestine. Methods GC modulation was assessed using qRT-PCR, western blotting and confocal microscopy. DSS colitis was induced in wild-type, TFF3−/− and TLR2−/− mice. Recombinant TLR2 ligand or TFF3 peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(166 citation statements)
references
References 39 publications
(67 reference statements)
8
155
2
1
Order By: Relevance
“…HIEC play a central role in absorptive and secretory functions, protecting the organisms from bacteria and toxins, providing an effective barrier against the complex antigenic load of intestinal contents (3,25). However, difficulties still exist in establishing an HIEC cell line in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIEC play a central role in absorptive and secretory functions, protecting the organisms from bacteria and toxins, providing an effective barrier against the complex antigenic load of intestinal contents (3,25). However, difficulties still exist in establishing an HIEC cell line in China.…”
Section: Discussionmentioning
confidence: 99%
“…Published May 14, 2010. Epithelial cells lining the intestinal mucosa play a key role in the homeostasis of the organisms (1,2). Depending on their location in the intestinal tract, they not only play a central role in absorptive and secretory functions, but also have the ability to protect the organism from various pathogens and toxins found even under the normal conditions in the intestine, providing an effective barrier to the complex antigenic load of intestinal contents (3). In addition, some of the most serious pathological conditions, such as inflammatory bowel disease (IBD), are known to be associated with alterations of the normal growth and functions of the intestinal epithelium (4).…”
Section: Introductionmentioning
confidence: 99%
“…This result was particularly interesting since TLR2 has been associated with severe forms of UC implicating its role as a modifier in inflammatory bowel diseases. 39 Overall, we could conclude that the genetic deficiency of a molecule with distinctive roles in bacterial pattern recognition (Tlr2) induces a comprehensive response at the level of the colonic mucosa that involves the reconstitution of both the epithelial transcriptional network (including epigenetic modifications) and the associated microbiota. This reconstitution is likely sensitive to the genetic background of the host and may be responsive to nutritional exposures (such as folate supplementation) during specific stages of development.…”
Section: The Remarkable Adaptation Of the Colonic Mucosa To Toll-likementioning
confidence: 94%
“…TLR-4 has been the most frequently studied in NEC models, and it is suggested that activation of TLR-4 signaling leads to increased intestinal injury (22,27,30). In colitis models, TLR-2 protects intestinal mucosa against injury via regulation of epithelial apoptosis (3,4,36), and, recently, a role for TLR-2 in NEC pathogenesis was also suggested (30,41). However, the role of TLR-2 in probiotics-mediated protection against NEC is not known.…”
mentioning
confidence: 99%